Symptom variability over the course of the day in patients with stable COPD in Brazil: A real-world observational study - Cukier, Alberto; De Godoy, Irma [UNESP]; Costa, Claudia Henrique da; Rubin, Adalberto Sperb; Gregorio, Marcelo Gervilla; Neto, Aldo Agra de Albuquerque; Lima, Marina Andrade; Pereira, Monica Corso; Tanni, Suzana Erico [UNESP]; Athanazio, Rodrigo Abensur; Bessa, Elizabeth Jauhar Cardoso; Wehrmeister, Fernando Cesar; et al. (Sociedade Brasileira de Pneumologia e Tisiologia, 2020)
Objective: To analyze symptoms at different times of day in patients with COPD. Methods: This was a multicenter, cross-sectional observational study conducted at eight centers in Brazil. We evaluated morning, daytime, and nighttime symptoms in patients with stable COPD. Results: We included 593 patients under regular treatment, of whom 309 (52.1%) were male and 92 (15.5%) were active smokers. The mean age was 67.7 years, and the mean FEV1 was 49.4% of the predicted value. In comparison with the patients who had mild or moderate symptoms, the 183 (30.8%) with severe symptoms were less physically active (p = 0.002), had greater airflow limitation (p < 0.001), had more outpatient exacerbations (p = 0.002) and more inpatient exacerbations (p = 0.043), as well as scoring worse on specific instruments. The most common morning and nighttime symptoms were dyspnea (in 45.2% and 33.1%, respectively), cough (in 37.5% and 33.3%, respectively), and wheezing (in 24.4% and 27.0%, respectively). The intensity of daytime symptoms correlated strongly with that of morning symptoms (r = 0.65, p < 0.001) and that of nighttime symptoms (r = 0.60, p < 0.001), as well as with the COPD Assessment Test score (r = 0.62; p < 0.001), although it showed only a weak correlation with FEV1 (r = −0.205; p < 0.001). Conclusions: Dyspnea was more common in the morning than at night. Having morning or nighttime symptoms was associated with greater daytime symptom severity. Symptom intensity was strongly associated with poor quality of life and with the frequency of exacerbations, although it was weakly associated with airflow limitation.
Keywords: Brazil; Chronic obstructive; Disease progression; Pulmonary disease; Quality of life; Respiratory; Signs and symptoms